Financial Performance Strategy: Interaksi Human Capital dan Social Performance - Richo Diana Aviyanti; Indra Ayu Fatmala; Nanda Avrellia Putri (Jurnal Akademi Akuntansi, 2024)
Purpose: The study aimed to determine the effects of corporate social responsibility, strategi manajemen, dan green human capital on financial performance. Methodology/approach: This study uses a quantitative approach with a positivism paradigm. The population is all issuers listed on the Indonesia Stock Exchange for the 2020-2022 period, totaling 712 companies. Sampling used a purposive sampling method with a total observation (N) of 936 companies. Methods of data analysis using multiple regression analysis with the SPSS tool. Findings: Management strategy and green human capital affect financial performance. Management strategy can increase competitive advantage which has an impact on financial performance. Information from corporate social responsibility activities is not affect financial performance. Practical and Theoretical contribution/Originality: This research contributes to confirming resources based view theory and provides additional empirical evidence regarding the affect of corporate social responsibility, management strategy, and green human capital on financial performance and broadens generalizations. Strategic decision making and management strategy determination must be directed at creating a unique competitive advantage and commitment to human resource management.